Optimalisasi Literasi Ekonomi Digital Berbasis Kearifan Lokal dalam Meningkatkan Daya Saing Ekonomi - Masithoh, Fitria Nur; Syam, Andi Zulitsnayarti Mardhani (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This research focuses on optimizing digital economic literacy based on local wisdom to enhance economic competitiveness within the Peh-Preneur community in Kediri. The study aims to understand how integrating local wisdom with digital literacy can strengthen the business performance of local entrepreneurs. A qualitative approach was used, combining interviews, observations, and document analysis to gather data from the community. The findings reveal that local wisdom, such as traditional values of cooperation and sustainability, adds unique value to local products and can significantly increase their appeal in both local and global markets. Digital economic literacy, particularly in areas like e-commerce, social media marketing, and digital payment systems, enables entrepreneurs to expand their market reach, improve operational efficiency, and compete more effectively. However, challenges in technology access and digital literacy remain. The study concludes that digital literacy, combined with local wisdom, offers substantial opportunities to enhance competitiveness, but requires ongoing support in training and infrastructure development for optimal outcomes.